Research on channel state collection system for high-dynamic wireless networks - Zhang Hongyun; Peng Jinlin; Lin Bo (Dianzi Jishu Yingyong, 2025)
In high-dynamic wireless networks, typically represented by Wireless Body Area Networks (WBANs), recording the state of wireless channels with high temporal precision is a critical preliminary issue for conducting research on transmission optimization schemes. With low cost and portability as core objectives, this paper comprehensively compares several typical wireless development components and selects ESP32+ESP-NOW as the hardware and software development platform. It also designs a set of high-precision wireless channel state collection and recording systems. After design optimization, this hardware and software system can achieve a maximum transmission interval of approximately 257 microseconds. Additionally, through multiple sets of experimental tests controlling variables, the effects of protocol mode, transmission rate, number of cores, thread count, CPU frequency, serial communication, and file read/write on packet transmission intervals and stability were evaluated in detail. The research findings of this paper provide design schemes and test data references for related research in the field of high-dynamic wireless networks.